Meningkatkan Hasil Belajar Muatan PPKn Menggunakan Model Pembelajaran PBL, STAD, dan Talking Stick Pada Siswa Kelas IV SDN Kelayan Timur 5 Banjarmasin - Yasmin Pitiyanova; Ahmad Muhyani Rizalie (CV. ITTC INDONESIA, 2024)
The problem raised in this study is the low learning outcomes of fourth grade students at SDN Kelayan Timur 5 Banjarmasin on PPKn content. The causes of these problems are learning that does not trigger students' skills in critical thinking, learning is only centered on teachers and theme books, and lack of motivation and interest in student learning. The effort made to address this issue is by using a combination of PBL, STAD, and Talking Stick models. The research aims to describe the quality of teacher and student activities, as well as analyze the improvement in students' learning outcomes. A qualitative approach with Classroom Action Research (CAR) was conducted for three meetings at SDN Kelayan Timur 5 Banjarmasin during the 2022/2023 academic year, involving 25 fourth grade students. The research was carried out on the theme